Adenovirus interaction with distinct integrins mediates separate events in cell entry and gene delivery to hematopoietic cells. - Huang, S (1996)
A major impediment to the effective use of adenovirus vectors for gene therapy is a lack of knowledge of how these vectors interact with diverse cell types in vivo. Adenovirus attachment to most human cell types is mediated by the fiber protein, which binds to an as yet unidentified cell receptor. In contrast to this, we report that adenovirus type 2 (Ad2) attachment to hematopoietic cells is facilitated by interaction of the penton base protein with members of the beta2 integrin family. Adenovirus particles were capable of binding to human monocytic cells, which lack fiber receptors, and virus binding could be blocked by a soluble penton base or by a function-blocking monoclonal antibody to integrin alphaMbeta2. To confirm the role of alphaMbeta2 integrins in Ad2 binding to hematopoietic cells, we analyzed virus attachment and gene delivery to CHO cells expressing recombinant beta2 integrins. alphaMbeta2-expressing CHO cells supported 3- to 5-fold-higher levels of Ad2 binding and 5- to 10-fold-larger amounts of gene delivery than did nontransfected CHO cells, indicating that alphaMbeta2 facilitates adenovirus attachment to and infection of hematopoietic cells. While beta2 integrins promote Ad2 attachment to hematopoietic cells, further studies demonstrated that alphav integrins were required for the next step in infection, virus internalization into cell endosomes. These studies reveal a novel pathway of Ad2 infection of hematopoietic cells mediated by distinct integrins which facilitate separate events in virus entry. They also suggest a possible strategy for selective adenovirus-mediated gene delivery to hematopoietic cells.